Examining Heat Transfer Characteristics and Thermal Comfort of the Indoor Human Body at Different Activity Levels Under Solar Radiation Conditions - Liu Guodan; Qiao Meijie; Ji Yihang; Hu Songtao; Liang Shuwei; Zhao Yizhou; Wang Fulai; Ding Zhaoxiang (Zhileng xuebao, 2024)
Solar radiation is a significant factor affecting indoor air-conditioning loads. When sunlight directly reaches the human body, it impacts the heat exchange between the body and the surrounding environment, consequently affecting thermal sensation. The change in temperature of an environment in which a body is in thermal neutrality is related to the energy consumption of the air-conditioning system and human thermal comfort. In this study, a winter experiment was conducted in an artificial climate chamber using a solar radiation simulation device to control the intensity of the solar radiation. The subjects wore typical clothing and performed sitting and walking tasks (at speeds of 3.2 km/h and 5 km/h). Physiological parameters and thermal sensation questionnaires were analyzed to determine the heat exchange characteristics between the bodies and the surrounding environment under the combined effects of solar radiation and different activity levels. Furthermore, the displacement law of the thermal comfort zone was examined. The results showed that, compared with the case of solar radiation, as the activity level increased, the proportion of evaporation heat exchange increased, the proportions of convective heat exchange and radiant heat exchange decreased, the thermal comfort zone shifted downward, and the environmental temperature required to maintain a comfortable state in winter decreased. This study provides a reference for design parameters to improve the efficiency of air-conditioning systems.